Transversus Abdominis Plane Block in Colorectal Surgery: A Meta-Analysis - Viderman, Dmitriy; Aubakirova, Mina; Abdildin, Yerkin G. (Frontiers in Medicine, 2022)
Acute postoperative pain is one of the most common concerns in the early postoperative period in colorectal surgery. Opioids still represent the cornerstone of postoperative pain management, yet they often result in significant side effects such as nausea and/or vomiting, sedation, urinary retention, delayed recovery of colonic motility, respiratory depression, and postoperative ileus. Transversus abdomins plane (TAP) block has been widely used for postoperative analgesia in various abdominal surgeries. The primary aim of this meta-analysis was to compare postoperative opioid requirements between the TAP block and control (placebo) group. The secondary aims included evaluation of the efficacy of TAP block in postoperative pain management, time to first request for opioids, length of hospital stay (LoS), and postoperative nausea and/or vomiting. We sought articles reporting the results of randomized controlled trials on the application of Transversus Abdominis Plane block in colorectal surgery published before September 2021. Eight RCTs reporting 615 patients were included in the meta-analysis. Seven articles reported the results of TAP block in laparoscopic surgery, one article reported the results on TAP block in open colorectal surgery, and one article focused on both laparoscopic and open surgery. The need for opioids within 24 hours after surgery, the intensity of pain at rest and when coughing, and postoperative nausea and vomiting was significantly lower in the TAP block compared to the “no block” group. There were no significant statistical differences in the overall pain score (over the entire hospital stay) and length of hospital stay after pooling the results of the TAP block versus the no block group.